2009
DOI: 10.1002/hbm.20783
|View full text |Cite
|
Sign up to set email alerts
|

No gender differences in brain activation during the N‐back task: An fMRI study in healthy individuals

Abstract: Gender differences have been well established in verbal and spatial abilities but few studies have examined if these differences also extend into the domain of working memory in terms of behavioural differences and brain activation. The conclusions that can be drawn from these studies are not clear cut but suggest that even though gender differences might not be apparent from behavioural measures, the underlying neural substrate associated with working memory might be different in men and women. Previous resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
55
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 15 publications
10
55
3
Order By: Relevance
“…Contrary to the results of the study by Li et al, women outperformed men in both tasks in this study, even in the more difficult version (2-back). In contrast, when testing with letters (Schmidt et al 2009), words and faces (Haut and Barch 2006), neither behavioral nor functional activation (with fMRI) differences were observed between the sexes. In the visuospatial domain, one study (Lejbak et al 2011) observed that men outperformed women in the n-back task.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Contrary to the results of the study by Li et al, women outperformed men in both tasks in this study, even in the more difficult version (2-back). In contrast, when testing with letters (Schmidt et al 2009), words and faces (Haut and Barch 2006), neither behavioral nor functional activation (with fMRI) differences were observed between the sexes. In the visuospatial domain, one study (Lejbak et al 2011) observed that men outperformed women in the n-back task.…”
Section: Introductionmentioning
confidence: 72%
“…Moreover, men were faster than women in all the tasks, denoting that even when discrimination levels are equivalent between sexes, men achieve this performance in shorter time. The majority of the studies (e.g., Schmidt et al 2009;Goldstein et al 2005;Speck et al 2000) failed to find sex differences in working memory reaction times. However, in tasks from the visuospatial domain, there is some evidence that men are faster than women (Loring-Meier and Halpern 1999).…”
Section: Reaction Timesmentioning
confidence: 98%
“…Using near-infrared spectroscopy in 50 participants, predominant left-hemispheric activations were also found in females, while performance was equal compared to males in this study [21]. However, two further studies using fMRI in larger samples did not find any consistent sex differences, either on the behavioral or on the brain level [22] (n = 50), [27] (n = 49 + 61). The only study to date that used a so-called Sternberg task to investigate gender effects on the neural representations of WM (n = 33) also did not find differences in task performance.…”
Section: Discussionmentioning
confidence: 93%
“…While some authors did not find gender effects on WM task performance [19,20,21,22], others reported differences between the sexes [23,24]. The same is true for the corresponding brain activations which also were found to differ in some [19,20,21,23,25] but not all studies [22,26,27]. Besides the use of different WM paradigms (N-back, Sternberg item recognition tasks) and domains (spatial, verbal), again the fact of sometimes very small and inhomogeneous samples is likely to have contributed to these inconsistencies.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of gender differences, a female advantage in episodic memory retrieval is predominantly reported (e.g., Geffen, Moar, O'Hanlon, Clark, & Geffen, 1990;Herlitz, Nilsson, & Bäckman, 1997;Herlitz & Rehnman, 2008;Hultsch, Masson, & Small, 1991). However, there are mixed findings about the presence of gender differences in WM (Loring-Meier & Halpern, 1999;Lynn & Irwing, 2008;Schmidt et al, 2009).…”
mentioning
confidence: 99%